Multimodal presentation of E-commerce product reviews and ratings: empirical investigation using multimodality - Rajab Ghandour (Journal of Trade Science)
Purpose – The aim of the research is to evaluate different modality for product reviews presentation and its impact on users’ performance, purchase intention and enjoyment. Design/methodology/approach – The study utilized an experimental approach with 48 opportunistic participants in three groups (16 users per group). Participants were randomly assigned to experimental conditions to ensure unbiased treatment. Data were collected through controlled interventions or manipulations, with pre-defined measures to assess specific outcomes. Statistical techniques such as ANOVA were employed to analyse the data, allowing for comparisons between experimental variables. Findings – The findings revealed that integrating facial expression avatars and emojis into an e-commerce platform effectively communicates product reviews and ratings. Moreover, the use of animation significantly enhanced user enjoyment. This suggests that visual representations not only convey information effectively but also contribute to a more engaging and enjoyable user experience. Research limitations/implications – While this experiment offers valuable insights into the impact of different e-commerce presentation layouts on user behaviour, further research could delve deeper into specific aspects such as the influence of individual user characteristics and the long-term effects of layout preferences. Originality/value – This study contributes original insights by demonstrating the efficacy of facial expressive avatars and emojis in conveying product reviews and ratings within e-commerce platforms. Moreover, it adds value by highlighting the positive impact of animation on user enjoyment. By combining these elements, the research offers a novel approach to enhancing user engagement and understanding of customer feedback in online shopping environments. The findings provide valuable guidance for e-commerce platforms seeking innovative ways to communicate product information effectively and enhance the overall user experience, ultimately benefiting both businesses and consumers.